Investigating the morphology of bulk heterojunctions by laser photoemission electron microscopy - Falk Niefind; Rishi Shivhare; Stefan C.B. Mannsfeld; Bernd Abel; Mike Hambsch (Polymer Testing, 2022)
The nanoscale morphology of bulk heterojunctions is highly important for the charge dissociation and transport in organic solar cells and ultimately defines the performance of the cell. The visualization of this nano-morphology in terms of domain size and polymer orientation in a fast and straightforward way is therefore of great interest to evaluate the suitability of a film for efficient solar cells. Here, we demonstrate that the morphology of different blends of poly(3-hexylthiophene-2,5-diyl) (P3HT) and phenyl-C61-butyric acid methyl ester (PCBM) can be imaged and analyzed by employing photoemission electron microscopy.